2021
DOI: 10.1037/xan0000293
|View full text |Cite
|
Sign up to set email alerts
|

Controlling for dogs’ (Canis familiaris) use of nonmnemonic strategies in a spatial working memory task.

Abstract: Short assessments of spatial working memory (SWM) in dogs are becoming popular evaluations of canine aging and individual differences. In a typical SWM task, an experimenter hides a reward inside of a bucket at a specific stimulus position while the dog watches. Then, following a varying delay interval, the dog is released to choose a bucket. The longest delay at which the dog can successfully choose the bucket containing the reward is considered to reflect the dog's SWM duration. Although past studies were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…This finding contrasts our hypothesis that performance across tasks would be related, which would have suggested that both tasks were measuring aspects of EF. Previous studies have used these tasks as measures of EF in dogs (Bray et al 2021 ; Foraita et al 2021b ; Krichbaum et al 2021 ; Lazarowski et al 2020b ; Osthaus et al 2010 ); however, some studies also found no relationships between these two tasks (Lazarowski et al 2020 ) or other tasks purported to measure similar aspects of EF (Foraita et al 2021b ), while others either only used one task (Krichbaum et al 2021 ; Osthaus et al 2010 ) or did not evaluate relationships between tasks (Bray et al 2021 ). Several studies have even found that tasks expected to measure the same component of EF, namely inhibitory control, exhibit no relationships between each other (Bray et al 2014 ; Brucks et al 2017 ; Fagnani et al 2016 ; Vernouillet et al, 2018), with other factors such as variations in task demands influencing performance across tasks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding contrasts our hypothesis that performance across tasks would be related, which would have suggested that both tasks were measuring aspects of EF. Previous studies have used these tasks as measures of EF in dogs (Bray et al 2021 ; Foraita et al 2021b ; Krichbaum et al 2021 ; Lazarowski et al 2020b ; Osthaus et al 2010 ); however, some studies also found no relationships between these two tasks (Lazarowski et al 2020 ) or other tasks purported to measure similar aspects of EF (Foraita et al 2021b ), while others either only used one task (Krichbaum et al 2021 ; Osthaus et al 2010 ) or did not evaluate relationships between tasks (Bray et al 2021 ). Several studies have even found that tasks expected to measure the same component of EF, namely inhibitory control, exhibit no relationships between each other (Bray et al 2014 ; Brucks et al 2017 ; Fagnani et al 2016 ; Vernouillet et al, 2018), with other factors such as variations in task demands influencing performance across tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Reversal tasks are also used to measure flexibility because participants must shift responding in one direction in favor of responding in the opposite direction (Olsen 2018 ). The DST (other names include the visible displacement task, the delayed response task, and the object choice task) has previously been used as a measure of spatial working memory in dogs (Bray et al 2021 ; Foraita et al 2021b ; Krichbaum et al 2021 ). In this task, a reward is hidden in one of two or three locations, and the dog is released to make a choice after a specified delay.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vila et al (2021) discuss the use a novel 'hide-and-seek' task in preschool age children to study episodic-like memory; their work illustrates how memory dynamics can change over time in a manner not very unlike what has been demonstrated in other nonhuman research paradigms. The paper by Krichbaum et al (2021) discusses some of the methodological difficulties one faces in studying spatial cognition in canines. These authors introduce a method to control for intervening motor processes in accounting for spatially directed control in matching-to-sample tasks with dogs.…”
mentioning
confidence: 99%